1989
DOI: 10.1093/ndt/4.11.975
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Lipid Peroxidation in Haemodialysis Patients: Effects of Vitamin E Supplementation

Abstract: In haemodialysis patients, increased concentrations of malonyldialdehyde and decreased vitamin E content indicate lipid peroxidation in the platelets from oxidative damage. The same process has been described in red blood cells and in mononuclear cells in peripheral blood. However, platelet aggregation is within normal limits and does not change after treatment with vitamin E. On the other hand vitamin E supplementation reverts completely the biochemical abnormality of the platelets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Activation of the leukocytes dur ing the inflammatory reaction increases the generation of free radicals; some of these leak outside the cells and injure surrounding tissues. Because they have an extremely short life-span (a half life of a few milliseconds) free radicals are difficult to measure directly; instead we obtain indirect evidence of their toxic effects on biological tissues by measuring markers of lipid peroxidation, such as malondialdehyde or conjugated dienes [12,13]. In these studies we have found that, in rats infused intraperitoneally over 6 days with saline the concentration of MDA in lipids from the omentum had increased, suggesting that there was an augmented generation of free radicals within the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the leukocytes dur ing the inflammatory reaction increases the generation of free radicals; some of these leak outside the cells and injure surrounding tissues. Because they have an extremely short life-span (a half life of a few milliseconds) free radicals are difficult to measure directly; instead we obtain indirect evidence of their toxic effects on biological tissues by measuring markers of lipid peroxidation, such as malondialdehyde or conjugated dienes [12,13]. In these studies we have found that, in rats infused intraperitoneally over 6 days with saline the concentration of MDA in lipids from the omentum had increased, suggesting that there was an augmented generation of free radicals within the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TNF-␣ enhances the DNA binding of Cbfa1/Runx2, activated protein 1, and cAMP responsive element binding protein, which are important transcription factors in osteoblastic differentiation. [81][82][83][84][85][86][87][88][89][90] In addition to the osteogenic transdifferentiation of VSMCs, Demer and colleagues 91,92 highlighted the contributions of pluripotent vascular mesenchymal progenitors to the vascular calcium accrual. Calcifying cells of Demer are mural multipotent mesenchymal progenitors related to the microvascular pericyte.…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 99%
“…For example, the first five reports published in this area (1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992) are all from an Italian research group that administered 300 mg/day of intravenous a-tocopherol for 15 days and reported decreases in erythrocyte MDA, 38,39 peripheral blood mononuclear cell MDA, 40 and platelet MDA. 41 Articles from the same trial are highlighted with the same superscript symbol in Table 1.…”
Section: A-tocopherolmentioning
confidence: 99%